L01 Understanding the Health Care Experiences and needs of People Living with Huntingtons Disease (HD): An Exploratory Study. (17th September 2014) - Rae, D; McCann, S; Miedzybrodzka, Z
Abstract : Background: The complex and progressive nature of Huntington's disease (HD) mean that individuals, and their families affected by the condition require a variety of generic and specialist health and social services. However, it is recognised that the provision and delivery of services for HD patients is variable and very little is known about the experiences and views of patients and carers regarding their condition and support needs. Aims: The primary aim of this project was to improve understanding of the experiences and views of patients and carers affected by HD, and specifically to explore issues regarding their support needs. Methods: A qualitative approach using in-depth interviews with 7 HD patients and 6 family carers was used to explore their healthcare experiences and support needs. Results: Findings highlighted how prior experiences of the disease subsequently influence knowledge and understanding of the disease, as well as decision making about life choices and support needs. In particular, four key themes were identified: a) life prior to becoming symptomatic with HD, b) time of diagnosis, c) getting on with life with HD and d) concerns and planning for future care. Conclusions: This study emphasises the importance of a personalised approach which recognises the circumstances and needs for each HD patient and their family. By understanding patient and carer perspectives, health professionals would be better informed in the development of a more person-centred approach to meeting the multi-disciplinary support needs of HD patients and their carers'.